PENGARUH INTENSITAS KEBISINGAN AKTIVITAS PENERBANGAN TERHADAP KENYAMANAN KERJA PERSONIL AMC BANDAR UDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Gian Harits Pradipta; Kukuh Tri Prasetyo; Sudrajat (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
With the increasing demand for air transportation services, traffic and activities have also become increasingly crowded in the airspace and airport areas. People who live in the area around the airport certainly cannot avoid the noise that occurs in their area. For this reason airports need to pay attention to this matter, because the existence of an airport is expected to be able to provide positive synergy to the surrounding community and workers at the airport, by minimizing the impact that occurs due to noise. This study aims to ascertain whether the efforts made by the airport have fully met the standards in reducing the impact of flight activities at Sultan Aji Muhammad Sulaiman Sepinggan International Airport in accordance with the Regulation of the Minister of Manpower No. 13/MEN/X/2011. The method used in this study is descriptive quantitatively refers to the Decree of the Minister of Environment No. 48/MENLH/11/1996 on Raw Noise Levels as well as Regulation of the Minister of Manpower No. 13/MEN/X/2011 on Threshold Values for Noise. Data collection method using observation method, questionnaire and literature study. The result of this study is that the noise level that occurs has an influence of 68%. In addition, the comfort of work is also influenced by matters beyond research by 32%.